Evaluasi Perencanaan Proyek Pembangunan SDS X Menggunakan Network Diagram dan Crashing Project Guna Mengoptimalkan Waktu Dan Biaya Proyek - Ramadhan, Wahyu; Sitorus, Sutrisna; Maulana, Rizky (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The research focuses on evaluating the project time planning to know exactly when the project will be completed, the estimated budget to be spent, using the CPM and PERT methods to carry out an analysis of the SDS X Development Project Planning Evaluation. The results are with the CPM and PERT methods, the project's critical path is found in activities A – D – E – F – G – H – I – L – M – N with a project completion time using the CPM method is 52 days, while for the PERT method the project completion time is 54 days with a great chance of completing project work of 99, 94%. As for the results of the evaluation of cost planning using the crashing project method, it was found that there was an increase in costs of Rp. 6,902,000. So that the normal cost of a development project which is IDR 372,126.00 becomes IDR 379,028,000